Family Farming and the Solidarity Economy: Advances in Research - Torrente Castro, Willian; Martínez, Jarrison (Cooperativismo & Desarrollo, 2014)
This article presents the results of research that was part of the celebration of the International Year of Family Farming in 2014, in the specific case of the Association of Women Coffee Growers (Asociación de Mujeres Cafeteras) in the municipality of La Plata, Huila. The article shows the many contributions of family farming in Colombia, while stressing its potential to face the challenges of agriculture and food in the country, which can be boosted when dealt with through a social and solidarity organization. The research shows how family farming systems fulfil the following characteristics: legal landholding, hiring of labor at harvest times (the rest of the time they use family labor), the production system mixes the traditional with the innovative or technical, there is concern over soil conservation and environmental preservation, they have a commercial product as their economic backbone and simultaneously develop other productive systems for self-consumption and/or the market, also because multi-functionality requires them to have simultaneous access to multiple sources of resources, among others. Also, when shared needs are identified and there is a commitment to satisfy them, awareness is generated that family farming signifies great wealth for households. However, the work becomes more visible when there is a contribution to the development of each family and community through social and solidarity associativity.